2019
DOI: 10.2147/tcrm.s204860
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of atorvastatin with the risk of hepatotoxicity: a pilot prescription sequence symmetry analysis</p>

Abstract: Purpose This study aimed to evaluate Atorvastatin (ATO)-associated hepatotoxicity using prescription sequence symmetry analysis (PSSA), based on a health insurance database of a Chinese population living in Jiangsu Province, China. Methods Patients prescribed ATO and hepatoprotective drugs in 2017 were identified, and the run-in period was determined based on the “waiting-time” distribution. Adjusted sequence ratio (ASR) and 95% confidence interval (95% CI) were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…Drug-induced liver injury accounts for approximately 20% of inpatients with acute liver injury in China, owing to a wide use of traditional Chinese medicine and anti-tuberculosis drugs ( Li et al, 2007 ; Yu et al, 2017 ; Fang et al, 2016 ; Zhang et al, 2019 ). The marker drugs used in both studies, and also in our study, were recommended by the Chinese Medical Association guidelines for the treatment of DILI ( Yu et al, 2017 ), and they were widely used to treat liver injury in clinical practice ( Fang et al, 2016 ; Zhang et al, 2019 ). However, as a signal detection method, PSSA is vulnerable to bias and confounding existing in real-world data ( Davies et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drug-induced liver injury accounts for approximately 20% of inpatients with acute liver injury in China, owing to a wide use of traditional Chinese medicine and anti-tuberculosis drugs ( Li et al, 2007 ; Yu et al, 2017 ; Fang et al, 2016 ; Zhang et al, 2019 ). The marker drugs used in both studies, and also in our study, were recommended by the Chinese Medical Association guidelines for the treatment of DILI ( Yu et al, 2017 ), and they were widely used to treat liver injury in clinical practice ( Fang et al, 2016 ; Zhang et al, 2019 ). However, as a signal detection method, PSSA is vulnerable to bias and confounding existing in real-world data ( Davies et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The index drugs in our study are LEs, consisting of S-LEs, alternative-Les, and FO-LEs ( Table 1 ). The marker drugs are a group of hepatic protectors widely used in China with high specificity as the surrogate of liver injury, chosen by literature search, guideline recommendation, and clinical experience (expert consultation) ( Fang et al, 2016 ; Yu et al, 2017 ; Zhang et al, 2019 ), including anti-inflammatory agents, antioxidant agents, antidote agent, choleretics, cell membrane repair agents, and others ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular‐related prescribing cascades are considered high priority targets for deprescribing 9 . To date, seven statin‐related prescribing cascades have been described (Table S1 in the supplement) 10–17 . However, many of these cascades reflect known adverse events observed in large clinical trials or from spontaneous adverse event reporting and thus may have been expected.…”
Section: Introductionmentioning
confidence: 99%
“…Common side effects associated with statin therapy include arthralgia, myalgia, dyspepsia, weakness, and headache. In early clinical trials, elevations of liver enzymes were observed in up to 2% of patients; however, clinically apparent liver injury was rarely observed [1][2][3][4][5][6][7]. In the majority of cases, these mild elevations in liver enzymes were not clinically significant and rarely required discontinuation of therapy [8,9].…”
Section: Introductionmentioning
confidence: 99%